2008
DOI: 10.1016/j.ejphar.2007.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids shift arachidonic acid metabolism toward endocannabinoid synthesis: A non-genomic anti-inflammatory switch

Abstract: Glucocorticoids are capable of exerting both genomic and non-genomic actions in target cells of multiple tissues, including the brain, which trigger an array of electrophysiological, metabolic, secretory and inflammatory regulatory responses. Here, we have attempted to show how glucocorticoids may generate a rapid anti-inflammatory response by promoting arachidonic acidderived endocannabinoid biosynthesis. According to our hypothesized model, non-genomic action of glucocorticoids results in the global shift of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 231 publications
(237 reference statements)
2
48
0
3
Order By: Relevance
“…Furthermore, N-acylethanolamines other than AEA, which exhibit distinct saturated or unsaturated fatty acids and show no (or little) direct effect on CB receptors (i.e., linoleoyl ethanolamide (LEA), palmitoyl ethanolamide (PEA), oleoyl ethanolamide (OEA), stearoyl ethanolamide (SEA)), have been shown to act as ECs entourage molecules, possibly acting in concert with ECs [15][16][17][18]. Yet another important class of signaling lipids involves the steroids, which appear to functionally interlink the different AA lipid signaling networks, including the endocannabinoid system [19,20]. Steroids (glucocorticoids and mineralocorticoids) are involved in numerous physiological processes, including immunomodulation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, N-acylethanolamines other than AEA, which exhibit distinct saturated or unsaturated fatty acids and show no (or little) direct effect on CB receptors (i.e., linoleoyl ethanolamide (LEA), palmitoyl ethanolamide (PEA), oleoyl ethanolamide (OEA), stearoyl ethanolamide (SEA)), have been shown to act as ECs entourage molecules, possibly acting in concert with ECs [15][16][17][18]. Yet another important class of signaling lipids involves the steroids, which appear to functionally interlink the different AA lipid signaling networks, including the endocannabinoid system [19,20]. Steroids (glucocorticoids and mineralocorticoids) are involved in numerous physiological processes, including immunomodulation [21].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, interactions between endocannabinoids and the HPA axis are reciprocal. Studies have shown that glucocorticoids can activate the release of endocannabinoids, AEA and 2-AG [152]. Conversely, endocannabinoids act efficiently to regulate stress response, partly by modulating the glucocorticoid system [150,153].…”
Section: Pufas / Endocannabinoids Interactions In Mood and Anxiety DImentioning
confidence: 99%
“…It is known that females have higher basal corticosteroid levels and greater stress-induced corticosteroid secretion but slower corticosteroid clearance from circulation [8,9]. Chronic exposure to corticosterone, CB 1 agonists and cannabinoids has been shown to downregulate CB 1 receptor density, CB 1 receptor binding and CB 1 mRNA expression in brain regions such as cerebellum and hippocampus [15,22,26,37,41].…”
Section: Introductionmentioning
confidence: 99%